Applying a sustainability perspective in the literature on physical therapy in relation to pharmaceuticals: a scoping review - Svensson, Patric; Jacobsson, Magdalena; Palstam, Annie; Lange, Elvira (Frontiers in Public Health, 2025)
IntroductionPhysical therapy encompasses a broad range of treatment options, often utilized in clinical settings where pharmaceutical interventions are standard. The potential for physical therapy to contribute to sustainable healthcare by reducing environmental impact, while maintaining the quality of care, remains underexplored. This study aimed to map existing research comparing physical therapy to pharmaceuticals, with a specific focus on whether these studies address aspects of sustainable development.MethodsA scoping review was conducted, systematically searching the PubMed, Cinahl, and Pedro databases using keywords related to physical therapy, pharmaceuticals, and comparative studies. Two assessors independently reviewed and selected relevant studies, followed by data extraction and summarization of results.ResultsA total of 27 studies were included, varying in design, population, and healthcare context. The most commonly addressed conditions were osteoarthritis and musculoskeletal pain, with analgesics being the most frequently studied pharmaceutical interventions. While several studies touched upon economic and social dimensions of sustainable development, none examined environmental sustainability. This highlights a critical gap in current research.DiscussionFuture studies are needed to assess how physical therapy, when compared to pharmaceutical treatments, can contribute to sustainable healthcare by offering a low-carbon, resource-efficient alternative without compromising social sustainability through adverse effects. This knowledge could be instrumental in guiding healthcare systems toward more sustainable practices.Systematic review registrationA study protocol was registered in Open Science Framework 2023-03-31 (Available from: https://osf.io/we58g).